Plurinational Afrobolivianity: Afro-Indigenous Articulations and Interethnic Relations in the Yungas of Bolivia - Heck, Moritz (transcript, 2020)
In Bolivia's plurinational conjuncture, novel political articulations, legal reform, and processes of collective identification converge in unprecedented efforts to 're-found' the country and transform its society. This ethnography explores the experiences of Afrodescendants in plurinational Bolivia and offers a fresh perspective on the social and political transformations shaping the country as a whole. Moritz Heck analyzes Afrobolivian social and cultural practices at the intersections of local communities, politics, and the law, shedding light on novel articulations of Afrobolivianity and evolving processes of collective identification. This study also contributes to broader anthropological debates on blackness and indigeneity in Latin America by pointing out their conceptual entanglements and continuous interactions in political and social practice.